An organization‐ and category‐level comparison of diagnostic requirements for mental disorders in ICD‐11 and DSM‐5. Issue 1 (12th January 2021) - First, Michael B.; Gaebel, Wolfgang; Maj, Mario; Stein, Dan J.; Kogan, Cary S.; Saunders, John B.; Poznyak, Vladimir B.; Gureje, Oye; Lewis‐Fernández, Roberto; Maercker, Andreas; Brewin, Chris R.; Cloitre, Marylene; et al.
Abstract : In 2013, the American Psychiatric Association (APA) published the 5th edition of its Diagnostic and Statistical Manual of Mental Disorders (DSM‐5). In 2019, the World Health Assembly approved the 11th revision of the International Classification of Diseases (ICD‐11). It has often been suggested that the field would benefit from a single, unified classification of mental disorders, although the priorities and constituencies of the two sponsoring organizations are quite different. During the development of the ICD‐11 and DSM‐5, the World Health Organization (WHO) and the APA made efforts toward harmonizing the two systems, including the appointment of an ICD‐DSM Harmonization Group. This paper evaluates the success of these harmonization efforts and provides a guide for practitioners, researchers and policy makers describing the differences between the two systems at both the organizational and the disorder level. The organization of the two classifications of mental disorders is substantially similar. There are nineteen ICD‐11 disorder categories that do not appear in DSM‐5, and seven DSM‐5 disorder categories that do not appear in the ICD‐11. We compared the Essential Features section of the ICD‐11 Clinical Descriptions and Diagnostic Guidelines (CDDG) with the DSM‐5 criteria sets for 103 diagnostic entities that appear in both systems. We rated 20 disorders (19.4%) as having major differences, 42 disorders (40.8%) as having minor definitional differences, 10 disorders (9.7%) as having minor differences due to greater degree of specification in DSM‐5, and 31 disorders (30.1%) as essentially identical. Detailed descriptions of the major differences and some of the most important minor differences, with their rationale and related evidence, are provided. The ICD and DSM are now closer than at any time since the ICD‐8 and DSM‐II. Differences are largely based on the differing priorities and uses of the two diagnostic systems and on differing interpretations of the evidence. Substantively divergent approaches allow for empirical comparisons of validity and utility and can contribute to advances in the field.